PENERAPAN METODE LINE OF BALANCE (LOB) DALAM OPTIMALISASI JADWAL PEMBANGUNAN PERUMAHAN GRAHA ALAM SUTRA - Matoha, Anwar; Mohamad Januar Fuad; Ari Putra Rachman (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2025)
This study aims to apply and analyze the Line of Balance (LoB) method for scheduling the construction of 20 type 36/108 houses in the Graha Alam Sutra Housing Complex, Hutuo Village, Limboto District, Gorontalo Regency. The research questions include the technical application of the LoB method and the evaluation of project scheduling results after implementing the method. Research data includes the S-curve, Cost Estimate Plan (CEP), network planning, and field data. The LoB method is applied through the development of a Work Breakdown Structure (WBS), activity logic diagram, and LoB graph for one house unit, which is then scaled up to 20 units simultaneously and linearly. Adjustments were made to the RAB, S-curve, and work sequence to prevent conflicts (crosses) between activities. The research results show that the LoB method successfully identified the project's critical path, minimized time deviations, and improved work rotation efficiency and field supervision. The project was completed in 110 calendar days with balanced work distribution across weeks. In conclusion, the LoB method proved effective for large-scale housing construction projects, producing a more structured, efficient, and easily monitored schedule compared to conventional methods.